Amphiphilic weak-solvation low-temperature electrolyte and preparation method and application thereof
By constructing a weakly coordinated solvation structure through amphiphilic weak solvation low-temperature electrolyte, the problems of high lithium ion desolvation energy barrier and unstable interface SEI in lithium metal batteries at low temperatures are solved, efficient lithium ion transport and lithium dendrite suppression are achieved, and the low-temperature cycle performance and coulombic efficiency of the battery are improved.
Patent Information
- Application Number
- CN202511022522.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-24
- Publication Date
- 2025-10-17
AI Technical Summary
Traditional lithium metal batteries have high lithium ion desolvation energy barriers, unstable interface SEI, and low ion transfer efficiency in low-temperature environments, resulting in performance degradation.
By using an amphiphilic weak solvation low-temperature electrolyte and combining an amphiphilic weak solvent with a diluent, a weakly coordinated solvation structure is constructed to reduce the desolvation energy barrier of lithium ions and form an inorganic-dominated SEI/CEI film on the positive and negative electrode surfaces, thereby improving interface stability and ion transfer efficiency.
It significantly improves the coulombic efficiency and cycle stability of lithium metal batteries at low temperatures, inhibits the growth of lithium dendrites, and achieves long cycle performance. The initial discharge capacity is as high as 135.68mAh g-1, and the coulombic efficiency reaches 98.01% at -40°C and as high as 99.38% at room temperature.
Smart Images

Figure CN120809962A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of lithium metal battery, and particularly relates to an amphiphilic weak-solvation low-temperature electrolyte and a preparation method and application thereof. BACKGROUND
[0002] Lithium metal batteries have become the mainstream energy storage carrier for portable electronic devices and electric vehicles due to their high energy density, long cycle life and environmental friendliness. However, in low-temperature environments, traditional lithium batteries face serious performance degradation problems: the ionic conductivity of the electrolyte decreases exponentially with temperature, leading to a sharp rise in battery resistance; the dynamic stability of the solid electrolyte interface (SEI) at the negative electrode interface deteriorates, and the lithium ion deintercalation barrier increases significantly; more critically, lithium metal negative electrodes or high-capacity silicon-based negative electrodes are prone to form dendrites or uneven lithium plating layers during low-temperature deposition, causing safety hazards and a sharp drop in capacity.
[0003] Current optimization strategies for low-temperature electrolytes mainly rely on low-viscosity solvents (such as carboxylic acid esters) and high-concentration lithium salt systems, which create a weak solvation effect by weakening the interaction between solvent molecules and solute ions, i.e., the interaction between solvent molecules and solute ions is relatively weak. This effect allows solute ions to migrate more freely in the solvent, thereby reducing ion transport resistance in low-temperature environments and mitigating the negative effects of low temperatures. However, the former sacrifices the high-temperature stability of the battery, and the latter significantly increases the cost and viscosity of the electrolyte. Traditional additives such as vinylene carbonate have a significantly weakened film-forming effect at low temperatures, making it difficult to effectively inhibit lithium dendrite growth. On the positive electrode side, the lithium ion diffusion rate of layered oxide materials such as NCM811 decreases by 1-2 orders of magnitude at low temperatures, causing a sharp rise in polarization voltage and a loss of reversible capacity. Existing thermal management techniques can alleviate low-temperature problems to some extent, but at the cost of sacrificing system energy density.
[0004] In summary, existing low-temperature electrolytes cannot simultaneously meet the multiple core requirements of "weak solvation effect-low temperature ion conduction-interface stability-high voltage compatibility", so it is necessary to design innovative solvation structures to enable efficient operation of lithium metal batteries in extreme low-temperature environments. SUMMARY
[0005] The present application provides an amphiphilic weak-solvation low-temperature electrolyte and a preparation method and application thereof, to overcome the problems of high lithium ion desolvation energy barrier, unstable interface SEI, and low ion transport efficiency of traditional electrolytes in low-temperature environments, as well as the performance degradation of lithium metal batteries in low-temperature environments in applications.
[0006] To achieve the above-mentioned purposes, the technical solutions of the embodiments of the present application are as follows:
[0007] The first aspect of the present application provides an amphiphilic weakly solvated low-temperature electrolyte, which is composed of an amphiphilic weak solvent, a lithium salt and a diluent;
[0008] One end of the amphiphilic weak solvent is an oxygen-containing group that can easily coordinate with lithium ions, and the other end is a hydrogen atom and a fluorine atom that weakly coordinate or do not coordinate with the lithium ions.
[0009] In combination with the first aspect, preferably, the amphiphilic weak solvent is one or more of 2,2,2-trifluoroethyl methyl sulfonate, 2,2,2-trifluoroethyl trifluoromethyl sulfonate, 2,2-difluoroethyl methyl sulfonate, and 2,2-difluoroethyl trifluoromethyl sulfonate.
[0010] In combination with the first aspect, preferably, the lithium salt is one or more of lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, and lithium difluoro(oxalato)borate.
[0011] In combination with the first aspect, preferably, the diluent is one or more of 1,1,2,2-tetrafluoroethyl-2,2,2,3-tetrafluoropropyl ether, 2,2,2-trifluoroethyl-1,1,2,2-tetrafluoroethyl ether, 1,1,2,2-tetrafluoroethyl methyl ether, and 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether.
[0012] In combination with the first aspect, preferably, the molar concentration of the lithium salt is 1-1.5 mol / L.
[0013] In combination with the first aspect, preferably, the volume ratio of the amphiphilic weak solvent to the diluent is 1:0.25-2.
[0014] The second aspect of the present application provides a preparation method of the amphiphilic weakly solvated low-temperature electrolyte of the first aspect, which comprises: dissolving a lithium salt in an amphiphilic weak solvent under an argon atmosphere, stirring until uniform, adding a diluent, and mixing until uniform to obtain the amphiphilic weakly solvated low-temperature electrolyte.
[0015] The third aspect of the present application provides an application of the amphiphilic weakly solvated low-temperature electrolyte of the first aspect or the amphiphilic weakly solvated low-temperature electrolyte prepared by the method of the second aspect in a lithium metal battery.
[0016] In combination with the third aspect, preferably, the lithium metal battery is a lithium sheet half-cell, which comprises LiNi 0.8 Co 0.1 Mn 0.1 O2 positive electrode material, a lithium sheet negative electrode, an aluminum foil current collector, a PP separator, and the amphiphilic weakly solvated low-temperature electrolyte.
[0017] Preferably in combination with the third aspect, the lithium metal battery has a charge-discharge voltage range of 2.5-4.4 V, and the charge-discharge cycle is carried out in a high-low temperature box, and the working temperature is -40-25 DEG C.
[0018] Compared with the prior art, the advantages or beneficial effects of the embodiments of the present application at least include:
[0019] (1) By the "lithiumophilic-lithiophobic" amphiphilic structure of the amphiphilic weak solvent and the low polarity characteristics of the diluent, a weak coordination solvation structure is constructed, which significantly reduces the desolvation energy barrier of lithium ions, thereby facilitating the desolvation process at low temperature.
[0020] (2) The amphiphilic weak solvation low-temperature electrolyte has better compatibility with the lithium metal negative electrode, which is beneficial to the uniform deposition of lithium metal and improves the coulombic efficiency. The coulombic efficiency of the Li||Cu battery at -40 DEG C is as high as 98.01%, and the coulombic efficiency of the Li||Cu battery at room temperature is as high as 99.38%.
[0021] (3) An inorganic-based SEI / CEI is formed on the surface of the positive and negative electrodes, which inhibits the growth of lithium dendrites and reduces the generation of positive electrode cracks. In addition, the electrolyte can realize long cycle of lithium metal battery at -40 DEG C, and the initial discharge capacity can be as high as 135.68 mAh g -1 . BRIEF DESCRIPTION OF DRAWINGS
[0022] Figure 1 Desolvation activation energy image of the low-temperature electrolyte of the lithium metal battery prepared in Example 1 and the comparative example;
[0023] Figure 2 Cycle performance diagram of the Li / Li symmetric battery of the low-temperature electrolyte of the lithium metal battery prepared in Example 1 and the comparative example at -40 DEG C;
[0024] Figure 3 Cycle performance diagram of the Li / NCM811 battery of the low-temperature electrolyte of the lithium metal battery prepared in Example 1 at -40 DEG C;
[0025] Figure 4 Coulombic efficiency diagram of the Li / Cu battery of the low-temperature electrolyte of the lithium metal battery prepared in Example 1 and the comparative example at -40 DEG C;
[0026] Figure 5 (a) and (b) are SEM images of the lithium metal deposition morphology of the amphiphilic weak solvation low-temperature electrolyte prepared in Example 1 and the comparative example at -40 DEG C;
[0027] Figure 6Cycling performance of Li / NCM811 symmetric battery at room temperature of the amphiphilic weakly solvating low-temperature electrolyte prepared for Example 1 and the comparative example;
[0028] Figure 7 (a) and (b) are SEM images of NCM811 positive electrode material after 100 cycles of lithium metal battery at-40℃ of the lithium metal battery low-temperature electrolyte prepared for Example 1 and the comparative example, respectively;
[0029] Figure 8 Coulomb efficiency of Li / Cu battery at room temperature of the lithium metal battery low-temperature electrolyte prepared for Example 1 and the comparative example. DETAILED DESCRIPTION
[0030] In order to make the objects, technical solutions and advantages of the present application clearer, the following will further describe the present application in conjunction with the accompanying drawings, and the described embodiments should not be regarded as limiting the present application. All other embodiments obtained by those of ordinary skill in the art without creative labor fall within the scope of protection of the present application.
[0031] In the following description, “some embodiments” are described, which describe a subset of all possible embodiments, but it can be understood that “some embodiments” can be the same subset or different subsets of all possible embodiments, and can be combined with each other without conflict. Unless otherwise defined, all technical and scientific terms used in the embodiments of the present application have the same meaning as understood by those skilled in the art to which the embodiments of the present application belong. The terms used in the embodiments of the present application are only for the purpose of describing the embodiments of the present application and are not intended to limit the present application.
[0032] In the following description of the embodiments of the present application, the terms “include”, “contain”, “have” and “comprise” and the like are all open terms, that is, they mean including but not limited to.
[0033] It should be noted that all raw materials / reagents in the embodiments of the present application can be purchased on the market or prepared according to conventional methods well known to those skilled in the art; the term “and / or” in the embodiments of the present application is only used to describe the association relationship of the associated objects, which means that there can be three relationships, for example, A and / or B means that there are three cases of A alone, B alone, and A and B simultaneously, wherein A and B can be singular or plural, and the character “ / ” generally represents a “or” relationship between the associated objects before and after it.
[0034] In the following description of the embodiments, the term "at least one" means one or more, and the term "multiple" means two or more. "At least one of the following (a)" or the like means any combination of the items, including a single item or any combination of a plurality of items. For example, "at least one of a, b or c", or "at least one of a, b and c", can mean a, b, c, a-b (i.e., a and b), a-c, b-c, or a-b-c, where a, b, and c can be a single item or a plurality of items.
[0035] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of the serial numbers does not mean the order of execution, and some or all steps can be executed in parallel or in sequence, and the execution order of each process should be determined according to its function and inherent logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0036] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a" and "the" used in the embodiments of the present application and the appended claims are also intended to include the plural forms, unless the context clearly indicates otherwise.
[0037] Those skilled in the art should understand that in the embodiments of the present application, the numerical range should be understood as also specifically disclosing each intermediate value between the upper limit and the lower limit of the range. Each smaller range between any stated value and stated range, and any intermediate value of the stated value or between the stated range is also included in the present application. The upper limit and the lower limit of these smaller ranges can be independently included or excluded from the range.
[0038] Unless otherwise specified, the technical / scientific terms used herein have the same meaning as generally understood by those skilled in the art of the present application. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein can also be used in the embodiments or tests of the present application. All documents mentioned in the specification are generally incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of conflict between the content of the present application and any incorporated document, the content of the present application shall prevail.
[0039] It should be noted that all raw materials and / or reagents in the embodiments of the present application are purchased on the market or prepared according to conventional methods well known to those skilled in the art.
[0040] In a first aspect, the embodiments of the present application provide an amphiphilic weakly solvated low-temperature electrolyte, which is composed of an amphiphilic weakly solvated solvent, a lithium salt and a diluent.
[0041] The one end of the amphiphilic weak solvent is an oxygen-containing group that can coordinate with lithium ions, and the other end is a hydrogen atom and a fluorine atom that weakly coordinate or do not coordinate with the lithium ions.
[0042] In specific embodiments, the amphiphilic weak solvent is preferably one of 2,2,2-trifluoroethyl methanesulfonate, 2,2,2-trifluoroethyl trifluoromethanesulfonate, 2,2-difluoroethyl methanesulfonate, and 2,2-difluoroethyl trifluoromethanesulfonate.
[0043] It should be noted that one end of the amphiphilic weak solvent is an oxygen-containing group that can coordinate with lithium ions. This oxygen-containing group can form moderate coordination with lithium ions, providing the necessary solvation environment for lithium ions and ensuring the ionic conductivity of the low-temperature electrolyte. Here, the oxygen-containing group includes but is not limited to ether bond (-O-), hydroxyl (-OH), carbonyl (C=O), ester (-COO-), etc. Such groups have moderate electron cloud density and can form coordination bonds with lithium ions Li + through lone pair electrons, but the coordination energy is lower than that of traditional strong solvents (such as the carbonate group in ethylene carbonate (EC)), avoiding the formation of an overly stable solvation sheath.
[0044] The other end is a weakly coordinated / non-coordinated group containing hydrogen atoms and fluorine atoms, which weakens the interaction with lithium ions and avoids excessive solvation of lithium ions. The strong electronegativity of the fluorine atom reduces the polarity of the end group, significantly weakening the electrostatic interaction with Li + ; the hydrogen atom can improve the compatibility with other components in the electrolyte, such as diluents and lithium salt anions, through van der Waals forces, ensuring uniform dispersion of the molecules in the system.
[0045] In the present application, the unique group structure of the amphiphilic weak solvent can provide the necessary solvation environment for lithium ions to maintain ionic conduction, without excessive solvation of lithium ions. This weak solvation property can reduce the energy barrier of lithium ion desolvation at low temperatures, facilitating the migration of lithium ions in a low-temperature environment and improving the low-temperature performance of the electrolyte.
[0046] In specific embodiments, the lithium salt is preferably one of lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, and lithium difluoro(oxalato)borate.
[0047] It should be noted that the lithium salt in the low-temperature electrolyte serves to provide lithium ions, which is the basis for the ionic conductivity of the electrolyte. The dissociated lithium ions are the carriers of charge transfer in the battery charging and discharging process. In selecting the lithium salt, the present application considers its solubility, dissociation degree, and chemical stability in the amphiphilic weak solvent and diluent.
[0048] In specific embodiments, the molar concentration of the lithium salt is preferably 1-1.5 mol / L.
[0049] It should be noted that when the molar concentration of lithium salt is too large, on the one hand, the excessive lithium salt will cause the interaction between ions in the electrolyte to be significantly enhanced, and lithium ions and anions are easy to form ion pairs or aggregates, thereby reducing the number of free lithium ions, hindering the migration of lithium ions, and causing the ionic conductivity to decrease. On the other hand, high concentration of lithium salt will greatly increase the viscosity of the electrolyte, especially in low temperature environment, the flowability of the electrolyte will become very poor, further weakening the diffusion ability of lithium ions, seriously affecting the low temperature charge-discharge efficiency of the battery. In addition, too high lithium salt concentration may exceed the solubility limit of the amphiphilic weak solvent and the diluent, causing part of the lithium salt to precipitate without completely dissociating, destroying the uniformity of the electrolyte, and even blocking the electrode pores, causing irreversible decay of the battery performance.
[0050] When the molar concentration of lithium salt is too small (such as less than 1 mol / L), first of all, the number of lithium ions available for migration in the electrolyte is insufficient, directly leading to low ionic conductivity, which cannot meet the demand for charge transfer during the charge-discharge process of the battery, resulting in the decrease of the rate performance of the battery. Secondly, in the weak solvation system, the coordination balance between lithium ions and amphiphilic weak solvents will be broken, and a small amount of lithium ions will be difficult to form stable solvation sheath, which may cause lithium ions to react with electrode materials during migration due to the lack of necessary solvation protection, aggravating the corrosion of the electrode and the decomposition of the electrolyte, and shortening the cycle life of the battery. At the same time, too low lithium salt concentration will also reduce the ionic strength of the electrolyte, affecting its compatibility with the electrode interface, which may lead to unstable formation of SEI film, further deteriorating the low temperature performance of the battery.
[0051] Therefore, the molar concentration of lithium salt is controlled in the preferred range of 1-1.5 mol / L, which can not only ensure sufficient free lithium ions in the electrolyte to maintain high ionic conductivity, but also avoid problems such as abnormal viscosity, ion aggregation and aggravated side reactions caused by too high or too low concentration, and form synergy with the weak solvation characteristics of the amphiphilic weak solvent, to jointly ensure the excellent performance of the electrolyte at low temperature.
[0052] In specific embodiments, the diluent is preferably one of 1,1,2,2-tetrafluoroethyl-2,2,2,3-tetrafluoropropyl ether, 2,2,2-trifluoroethyl-1,1,2,2-tetrafluoroethyl ether, 1,1,2,2-tetrafluoroethyl methyl ether, 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether.
[0053] In the present application, the diluent is mainly used to adjust the viscosity and dielectric constant of the electrolyte. By adding the diluent, the viscosity of the electrolyte can be reduced, and the flowability of the electrolyte at low temperature can be improved, thereby facilitating the migration of lithium ions. At the same time, the diluent can also adjust the dielectric constant of the electrolyte to a certain extent, affecting the dissociation and solvation process of lithium salt.
[0054] It should be noted that the diluent needs to have good mutual solubility with the amphiphilic weak solvent and lithium salt, and has extremely weak or no coordination ability with lithium ions to avoid interfering with the weak solvation characteristics of the amphiphilic weak solvent.
[0055] In specific embodiments, the volume ratio of the amphiphilic weak solvent to the diluent is preferably 1:0.25-2.
[0056] It should be noted that when the volume ratio is too large, i.e., the proportion of the amphiphilic weak solvent is more than 1:0.25, the proportion of the diluent is insufficient, and its viscosity-reducing effect cannot be fully exerted. At this time, the viscosity of the electrolyte will increase significantly, especially in a low-temperature environment, the viscous system will seriously hinder the migration channel of lithium ions, resulting in a significant decrease in ion diffusion rate. At the same time, too much amphiphilic weak solvent may strengthen the coordination with lithium ions. Although it has weak solvation characteristics itself, excessive aggregation will increase the thickness of the solvation sheath around lithium ions, thereby increasing the desolvation energy barrier and weakening the ion conduction efficiency at low temperature. In addition, too high a proportion of the amphiphilic weak solvent may also reduce the interfacial compatibility of the electrolyte with the electrode material, as there is not enough diluent to adjust the interfacial tension, which may lead to uneven formation of the SEI film on the electrode surface, affecting the cycle stability of the battery.
[0057] When the volume ratio is too small, i.e., the proportion of the diluent is too high, less than 1:2, the concentration of the amphiphilic weak solvent is excessively diluted, and its ability to provide a basic solvation environment for lithium ions will be greatly weakened. At this time, lithium ions may be difficult to form stable solvation structures due to the lack of sufficient oxygen-containing group coordination, resulting in a decrease in the number of free lithium ions and a decrease in ionic conductivity. More critically, excessive diluent (usually weakly polar or non-polar) will destroy the uniform dispersion of the amphiphilic weak solvent, which may cause phase separation of the system, and the amphiphilic weak solvent cannot maintain compatibility with the diluent due to its low concentration, forming local enrichment or stratification, and the electrolyte loses uniformity. This phase separation will cause the lithium ion conduction path to break, and especially at low temperature, the ionic conduction ability of the electrolyte will be sharply attenuated, and even the basic electrochemical performance will be lost.
[0058] Therefore, by controlling the volume ratio of the amphiphilic weak solvent to the diluent in the range of 1:0.25-2, the viscosity of the electrolyte can be reduced by the appropriate proportion of the diluent to ensure low-temperature fluidity, and the amphiphilic weak solvent can maintain sufficient concentration to provide a stable weak solvation environment, and the solvation ability and system fluidity are balanced, which is the key to achieving excellent low-temperature performance of the electrolyte.
[0059] In a second aspect, the embodiments of the present application provide a preparation method of the amphiphilic weakly solvated low-temperature electrolyte, which comprises: dissolving a lithium salt in an amphiphilic weak solvent under an argon atmosphere, stirring until uniform, then adding a diluent, mixing until uniform, and obtaining the amphiphilic weakly solvated low-temperature electrolyte.
[0060] It should be noted that the oxygen content of argon is <0.1 ppm, and the water content is <0.1 ppm.
[0061] In a third aspect, the embodiments of the present application provide an application of the amphiphilic weakly solvated low-temperature electrolyte of the first aspect or the amphiphilic weakly solvated low-temperature electrolyte prepared by the method of the second aspect in a lithium metal battery.
[0062] In specific embodiments, the lithium metal battery is a lithium sheet half-cell, which comprises LiNi 0.8 Co 0.1 Mn 0.1 O2 positive electrode material, a lithium sheet negative electrode, an aluminum foil current collector, a PP separator, and the amphiphilic weakly solvated low-temperature electrolyte.
[0063] In specific embodiments, the charge-discharge voltage range of the lithium metal battery is 2.5-4.4 V, and the charge-discharge cycle is carried out in a high-low temperature box, and the working temperature is -40-25℃.
[0064] The present application also provides the use of the low-temperature electrolyte of the lithium metal battery: the amphiphilic weakly solvated low-temperature electrolyte as a low-temperature electrolyte of a lithium metal battery with NCM811 as a positive electrode, for improving the discharge specific capacity, cycle life and a series of battery performances of the lithium metal battery under low-temperature conditions, under the low-temperature condition of -40℃, the lithium metal battery has an initial discharge specific capacity of 135.68 mAh g -1 , and after stable cycling for 500 cycles, the discharge specific capacity retention rate is 80.10% of the initial capacity; under normal temperature, the discharge specific capacity reaches 200.25 mAh g -1 after stable cycling for 100 cycles, the discharge specific capacity retention rate is 92.03% of the initial capacity.
[0065] (1) By the "lithiophilic-lithiphobic" amphiphilic structure of the amphiphilic weak solvent and the low polarity characteristics of the diluent, a weakly coordinated solvation structure is constructed, which significantly reduces the desolvation energy barrier of lithium ions, thereby facilitating the desolvation process at low temperature.
[0066] (2) The amphiphilic weakly solvated low-temperature electrolyte has better compatibility with the lithium metal negative electrode, is beneficial to uniform deposition of the lithium metal, and improves the coulombic efficiency. The coulombic efficiency of the Li||Cu battery is as high as 98.01% under a low-temperature condition of -40 DEG C, and the coulombic efficiency of the Li||Cu battery is as high as 99.38% at normal temperature.
[0067] (3) An inorganic-based SEI / CEI is formed on the surface of the positive and negative electrodes, the growth of lithium dendrites is inhibited, and the generation of positive electrode cracks is reduced. In addition, the electrolyte can realize long cycle of the lithium metal battery at -40 DEG C, and the initial discharge capacity can be as high as 135.68 mAh g -1 .
[0068] The technical method of the application will be further described below in combination with specific examples.
[0069] The raw materials used in the embodiments of the application are purchased from Suzhou Duoduo Chemical Technology Co., Ltd., Beijing Kaiguokong Technology Co., Ltd., Tianjin Zhongneng Lithium Industry Co., Ltd., and Dongguan Keluode Experimental Equipment Technology Co., Ltd.
[0070] In the following examples, CR2032 type button batteries are used to assemble button batteries. Specifically, it includes:
[0071] (1) In the lithium metal symmetric battery, the lithium sheet with a thickness of 500 microns is selected as the positive and negative electrodes, the diameter is 14 mm, the Celgard 2500PP separator with a thickness of 20 microns is selected as the separator, and the electrolyte dosage of each button battery is 70 microliters;
[0072] (2) In the lithium metal battery, the lithium sheet with a thickness of 500 microns is selected as the negative electrode, the loading amount of LiNi 2 Mn 0.8 Co 0.1 O2(NCM811) as the positive electrode is 9.2 mg / cm 0.1 , the Celgard 2500PP separator with a thickness of 20 microns is selected as the separator, and the electrolyte dosage of each button battery is 70 microliters.
[0073] Comparative example
[0074] The molar ratio of lithium bisfluorosulfonylimide, ethylene glycol dimethyl ether and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether is 1:1. The lithium salt concentration is 1 mol / L, and lithium bisfluorosulfonylimide 56.1063 mg, ethylene glycol dimethyl ether 150 microliters and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether 150 microliters are weighed according to the above ratio.
[0075] The lithium metal battery electrolyte is prepared by using the above-mentioned formula, and the steps are as follows: in an argon protection atmosphere glove box, the lithium salt is dissolved in ethylene glycol dimethyl ether, then 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether is added, and magnetic stirring is carried out until the mixture is uniform, and the lithium metal battery electrolyte is obtained.
[0076] Example 1
[0077] The present embodiment provides an amphiphilic weakly solvated low-temperature electrolyte 1, which is prepared from lithium salt, amphiphilic weak solvent and diluent; wherein the lithium salt is lithium bisfluorosulfonylimide (LiFSI) with a molar concentration of 1 mol / L. The amphiphilic weak solvent is 2,2,2-trifluoroethyl methanesulfonate, and the diluent is 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, and the volume ratio of the two is 1:1.
[0078] According to the molar concentration of lithium salt being 1 mol / L, and according to the volume ratio of 2,2,2-trifluoroethyl methanesulfonate to 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether being 1:1, lithium bisfluorosulfonylimide 56.1063 mg is weighed, 2,2,2-trifluoroethyl methanesulfonate 150 μL is measured, and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether 150 μL is measured.
[0079] The preparation method is as follows: in an argon protection atmosphere glove box, the lithium salt is dissolved in the amphiphilic weak solvent, then magnetic stirring is carried out until the mixture is uniform, and then the diluent is added, and the magnetic stirring is continued until the mixture is uniform, and the amphiphilic weakly solvated low-temperature electrolyte is obtained.
[0080] The test method is as follows:
[0081] (1) The electrolyte is used for Li / Li symmetric battery to test the desolvation activation energy, and the test method is as follows: the Li / Li symmetric battery is put into a high-low temperature box, and the temperature points are set as 30℃, 20℃, 10℃, -10℃, -20℃, -30℃ with 10℃ as the gradient, after the system temperature is balanced for 1h at each temperature point, EIS test is carried out, under the open circuit voltage condition, 5mV sinusoidal AC disturbance is applied, the frequency range is from 100kHz to 10mHz, the impedance spectrum is recorded, the impedance spectrum is fitted by using the equivalent circuit model, the desolvation activation energy is fitted according to the Arrhenius equation, and the test result is shown in Figure 1 , the desolvation activation energy of the symmetric battery of example 1 is lower than that of the comparative example, and example 1 has stronger desolvation capacity.
[0082] (2) The electrolyte is used for Li / Li symmetric battery to test the cycle performance, and the test conditions are as follows: under the condition of -40℃, 0.05mA / cm 2 of current density is selected, and the specific capacity is 0.05mAh / cm2 The constant current charge and discharge was carried out at the surface capacity of 0.5C. The test results are shown in Table 1. Figure 2 As shown in Table 1, the overpotential of the symmetrical battery of Example 1 is lower than that of the comparative example, and Example 1 has higher charge conduction ability and better cycle stability.
[0083] (3) The electrolyte was used for Li / NCM811 battery to test the cycle performance at low temperature, and the test conditions were as follows: at -40°C, 0.1C was charged to 4.4V, and then 0.1C was discharged to 2.5V, and the cycle was carried out at the above charge and discharge rate and voltage range. The test results are shown in Table 3. Figure 3 As shown in Table 3, at -40°C, the initial discharge capacity was 135.68 mAh g -1 , and after 500 cycles, the discharge capacity retention rate was 80.10% of the initial capacity.
[0084] (4) The electrolyte was used for Li / Cu battery to test the coulombic efficiency at low temperature, and the test conditions were as follows: at -40°C, Aurbach CE test was carried out at a current density of 0.05 mA / cm 2 . The test results are shown in Table 4. Figure 4 As shown in Table 4, at -40°C, the coulombic efficiency was 98.03%, and the SEM characterization of the lithium metal deposition morphology was carried out after the constant current discharge of the Li / Cu battery in Example 1 and the comparative example, and the results are shown in Table 5. Figure 5 As shown in Table 5, it was found that the lithium metal deposition morphology in the comparative example appeared dendritic, while no dendrite was generated in Example 1, and the deposition morphology was more uniform and dense.
[0085] (5) The electrolyte was used for Li / NCM811 battery to test the cycle performance at room temperature, and the test conditions were as follows: at room temperature, 0.5C was charged to 4.5V, and then 0.5C was discharged to 2.7V, and the cycle was carried out at the above charge and discharge rate and voltage range. The test results are shown in Table 6. Figure 6 As shown in Table 6, at room temperature, the initial discharge capacity was 200.25 mAh g -1 , and after 100 cycles, the discharge capacity was 184.29 mAh / g, and the cycle retention rate was 92.03%, and the SEM characterization of the positive electrode sheet after 100 cycles in Example 1 and the comparative example was carried out, and the results are shown in Table 7. Figure 7 As shown in Table 7, it was found that the NMC811 after cycle in the comparative example had cracks on the surface, while almost no cracks were generated in Example 1.
[0086] (6) The electrolyte was used for Li / Cu battery to test the coulombic efficiency at room temperature, and the test conditions were as follows: at room temperature, Aurbach CE test was carried out at a current density of 0.5 mA / cm 2 . The test results are shown in Table 8. Figure 8The coulombic efficiency is 99.38% at room temperature.
[0087] Example 2
[0088] The same as example 1, except that the lithium salt concentration is 1.25 mol / L, and the volume ratio of the two is 1:1.
[0089] According to the lithium salt molar concentration of 1.25 mol / L, according to the volume ratio of 2,2,2-trifluoroethyl methanesulfonate to 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether is 1:1, lithium bisfluorosulfonylimide 56.1063 mg, 2,2,2-trifluoroethyl methanesulfonate 150 μL, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether 150 μL.
[0090] The preparation method and the test method are the same as example 1.
[0091] Example 3
[0092] The same as example 1, except that the lithium salt concentration is 1.5 mol / L, and the volume ratio of the two is 1:1.
[0093] According to the lithium salt molar concentration of 1.5 mol / L, according to the volume ratio of 2,2,2-trifluoroethyl methanesulfonate to 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether is 1:1, lithium bisfluorosulfonylimide 84.1595 mg, 2,2,2-trifluoroethyl methanesulfonate 150 μL, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether 150 μL.
[0094] The preparation method and the test method are the same as example 1.
[0095] Example 4
[0096] The same as example 1, except that the lithium salt concentration is 1 mol / L, and the volume ratio of the two is 1:0.25.
[0097] According to the lithium salt molar concentration of 1 mol / L, according to the volume ratio of 2,2,2-trifluoroethyl methanesulfonate to 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether is 1:0.25, lithium bisfluorosulfonylimide 56.1063 mg, 2,2,2-trifluoroethyl methanesulfonate 240 μL, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether 60 μL.
[0098] The preparation method and the test method are the same as example 1.
[0099] Example 5
[0100] The same as example 1, except that the lithium salt concentration is 1 mol / L, and the volume ratio of the two is 1:0.5.
[0101] According to the lithium salt molar concentration is 1 mol / L, according to the volume ratio of 2,2,2-trifluoroethyl methyl sulfonate and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether is 1:0.5, lithium bisfluorosulfonylimide 56.1063 mg, 2,2,2-trifluoroethyl methyl sulfonate 200 μL, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether 100 μL.
[0102] The preparation method and the test method are the same as example 1.
[0103] Example 6
[0104] The same as example 1, except that the lithium salt concentration is 1 mol / L, and the volume ratio of the two is 1:2.
[0105] According to the lithium salt molar concentration is 1 mol / L, according to the volume ratio of 2,2,2-trifluoroethyl methyl sulfonate and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether is 1:2, lithium bisfluorosulfonylimide 56.1063 mg, 2,2,2-trifluoroethyl methyl sulfonate 100 μL, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether 200 μL.
[0106] The preparation method and the test method are the same as example 1.
[0107] The present application aims at the three core problems of high Li+ desolvation energy barrier, unstable interface SEI and low ion transmission efficiency of traditional electrolyte at low temperature, and proposes to construct a point-line type weak coordination solvation structure by complexing amphiphilic weak solvents, aiming to weaken the coordination between Li+ and solvent molecules, reduce the desolvation energy barrier, strengthen the interaction between Li+ and anions, and promote the formation of stable SEI film rich in inorganic components; and comprehensively reduce the viscosity, interface stability and high oxidation stability, while considering low temperature ion conduction, metal lithium negative electrode adaptation and high nickel positive electrode compatibility.
[0108] The design provides a new technical path to solve the problem of low temperature performance attenuation of lithium metal battery, which has great significance for strategic fields such as polar exploration, high-altitude equipment, electric transportation in cold regions, etc.
[0109] The above is only a specific embodiment of the present application, but the protection scope of the present application is not limited thereto, any skilled person in the art can easily think of changes or replacements within the technical range disclosed by the present application, which should be covered within the protection scope of the present application. Therefore, the protection scope of the present application should be subject to the protection scope of the claims.
Claims
1. An amphiphilic weakly solvated low-temperature electrolyte, characterized in that: The amphiphilic weak solvent low-temperature electrode liquid is composed of an amphiphilic weak solvent, a lithium salt and a diluent; One end of the amphiphilic weak solvent is an oxygen-containing group that is easily coordinated with lithium ions, and the other end is a hydrogen atom and a fluorine atom that are weakly coordinated or uncoordinated with the lithium ions.
2. The amphiphilic weakly solvated low-temperature electrolyte according to claim 1, characterized in that The amphiphilic weak solvent is one or more of 2,2,2-trifluoroethyl methanesulfonate, 2,2,2-trifluoroethyl trifluoromethanesulfonate, 2,2-difluoroethyl methanesulfonate, and 2,2-difluoroethyl trifluoromethanesulfonate.
3. The amphiphilic weakly solvated low-temperature electrolyte according to claim 1, characterized in that The lithium salt is one or more of lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, and lithium difluorooxalatoborate.
4. The amphiphilic weakly solvated low-temperature electrolyte according to claim 1, characterized in that The diluent is one or more of 1,1,2,2-tetrafluoroethyl-2,2,2,3-tetrafluoropropyl ether, 2,2,2-trifluoroethyl-1,1,2,2-tetrafluoroethyl ether, 1,1,2,2-tetrafluoroethyl methyl ether, and 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether.
5. The amphiphilic weakly solvated low-temperature electrolyte according to claim 1, characterized in that The molar concentration of the lithium salt is 1 to 1.5 mol / L.
6. The amphiphilic weakly solvated low-temperature electrolyte according to claim 1, characterized in that The volume ratio of the amphiphilic weak solvent to the diluent is 1:0.25-2.
7. A method for preparing the amphiphilic weakly solvated low-temperature electrolyte according to claims 1-6, characterized in that: include: Under an argon atmosphere, a lithium salt is dissolved in an amphiphilic weak solvent and stirred evenly, and then a diluent is added and mixed evenly to obtain an amphiphilic weak solvent low-temperature electrolyte.
8. Use of the amphiphilic weak solvate low-temperature electrolyte according to any one of claims 1 to 6 or the amphiphilic weak solvate low-temperature electrolyte prepared by the method according to claim 7 in a lithium metal battery.
9. The use according to claim 8, characterized in that The lithium metal battery is a lithium sheet half-cell, comprising LiNi 0.8 Co 0.1 Mn 0.1 O2 positive electrode material, lithium sheet negative electrode, aluminum foil current collector, PP separator and the amphiphilic weak solvent low-temperature electrolyte.
10. The use according to claim 9, characterized in that The charge and discharge voltage range of the lithium metal battery is 2.5 to 4.4 V. The charge and discharge cycle is carried out in a high and low temperature box with an operating temperature of -40 to -25°C.